Perubahan Material pada Kampung Romo Mangun Code Masa Lalu dan Masa Sekarang - Nabilah Ailsandira; Dinda Fauziah Djaelani; Hanif Budiman; Putu Ayu P. Agustiananda (Universitas Medan Area, 2026)
The diversity of materials that occur today in Kampung Romo Mangun-Code has aspects that do not meet the initial objectives of Romo Mangun himself. This study aims to identify what factors influence the changes in materials that occur significantly. This study uses a qualitative descriptive method. The descriptive research method is a method used to describe, interpret, a change that occurs, such as changes in materials that occur in houses in the Kampung Code settlement. Changes in materials that have changed such as construction, formerly wood, now concrete, walls that were originally bamboo have become bricks, and roofs that originally used clay tiles, while now metal roofs. Factors that influence such as lifestyle, adaptation to the environment, and economic factors. Future studies are expected to analyze the impact of modern materials used today.